Emotional Distress Correlates Among Patients With Chronic Nonspecific Low Back Pain: A Hierarchical Linear Regression Analysis. Issue 5 (12th March 2019) - Du, Shizheng; Hu, Yan; Bai, Yamei; Hu, Lingli; Dong, Jianshu; Jin, Shengji; Zhang, Heng
Abstract: Background: Chronic low back pain (CLBP) has become a worldwide health concern, and emotional distress is an important issue for CLBP management. However, it remains poorly understood how emotional distress happens and develops. This study aimed to systematically explore the correlates of emotional distress in patients with CLBP. Methods: The study was a multisite, cross‐sectional survey with a sample of 252 patients with CLBP in urban communities. A battery of questionnaires was used to collect data. Univariate analysis, Pearson correlation analysis, and hierarchical linear regression analysis were performed. Results: The mean score of emotional distress among 252 patients with CLBP was 13.85 ± 6.50. Hierarchical regression analysis indicated that the demographic factors, psychobehavioral factors, and social support of patients with CLBP were associated with their emotional distress, uniquely explaining 16.5%, 18.4%, and 6.2% of the variance, respectively. Five factors were found to be associated with patients' emotional distress: pain intensity (β = 0.257, P < 0.001), passive coping (β = 0.297, P < 0.001), active coping (β = −0.254, P < 0.001), self‐efficacy (β = −0.155, P = 0.005), and social support (β = −0.268, P < 0.001). Conclusions: Patients with CLBP suffered from clinically significant emotional distress. Patients' demographics, psychobehavioral factors, and social support were all related to emotional distress. The findings help us to identify the characteristics of patients with CLBP at high risk for emotional distress and to formulate corresponding countermeasures. Lay Summary: This study aimed to explored the correlates of emotional distress of patients with chronic low back pain (CLBP) by hierarchical linear regression analysis. The study found that patients' demographic factors, psycho‐behavioral factors, and social support were associated with their emotional distress, uniquely explaining 16.5%, 18.4%, and 6.2% of the variance, respectively. Pain intensity, passive coping, active coping, self‐efficacy, and social support were detected as significant correlates.